Chapter Violence and rape in the Italian fin-de-siècle: Gabriele D'Annunzio's "La Vergine Orsola" - Barisonzi, Michela (Biblioteca di Studi di Filologia Moderna, 2022)
This contribution discusses the representation of rape and violence against women in late 19th century Italian literature. In doing so, I focus on a short story, La Vergine Orsola, initially written by Gabriele D'Annunzio in 1884 as part of a short story collection titled Il Libro delle Vergini, later re-published in 1902 in Le Novelle della Pescara. This contribution looks at how the idea of rape is used in this short story as a narrative escamotage to bring to the attention of the reader the question of female entitlement to sexual desire as part of a social critique that D'Annunzio brings forward in his fin-de-siècle novels and short stories.